Pregnancy and reproductive healthcare among adolescent girls in the child welfare system - Font, Sarah; De Araujo Silva, Beatriz; Jones, Dylan (Frontiers in Pediatrics, 2025)
ObjectiveThis study examines the prevalence and predictors of first pregnancy and the use of long-acting reversible contraceptives (LARCs) among adolescent girls aged 12–17 involved in the child welfare system.MethodsThe study leverages linked longitudinal administrative data from the child welfare, juvenile legal, and Medicaid claims systems of Pennsylvania. The sample comprised 28,016 girls born between 2000 and 2005 who received Medicaid and were involved in the child welfare system during adolescence. Survival analysis was used to predict onset of first pregnancy and uptake of LARC.ResultsBy age 18, 17% percent of adolescents had experienced pregnant, with 18% having a healthcare encounter to receive LARCs. Foster care placement was not associated with pregnancy but was associated with increased use of LARCs. Substance use disorder, juvenile legal involvement, and recent suspected sexual abuse victimization were positively associated with pregnancy. There was a reciprocal association between LARCs and pregnancy; although any previous encounter for LARCs was negatively associated with pregnancy, uptake of LARCs also increased following a pregnancy.ConclusionsDespite broad reductions in teen pregnancy over time, adolescent girls with exposure to sexual abuse or engagement in substance use or delinquency face a persistently high risk for very early pregnancy. Medical providers and child welfare agencies need to coordinate service provision to address the sexual and reproductive health needs of at-risk teens.